A " Youth Multi-function Centre" in the Free State: An alternative to clinic-based HIV/AIDS prevention and care - C Heunis (AOSIS, 2000)
The youth are especially vulnerable to the HIV/AIDS epidemic in South Africa. In the Free State (second highest incidence of HIV/AIDS among the provinces), the Welkom-Goldfields area may for various reasons be singled out as a high risk area for HIV/AIDS which should receive priority attention in attempts to combat the disease. It is suggested that a Youth Multi-function Centre would place youth reproductive health care in the broader development and life skills arena - where it could be thought to rightfully belong. The objectives of the paper are to depict the rationale for a Youth Multi-function Centre, to broadly conceptualise a Youth Multi-function Centre, and to report on the process and methodology followed in an attempt to actually establish such a centre in Thabong/Welkom.